Surface Binding of Polypyrrole on Porous Silicon Hollow Nanospheres for Li‐Ion Battery Anodes with High Structure Stability. (22nd July 2014) - Du, Fei‐Hu; Li, Bo; Fu, Wei; Xiong, Yi‐Jun; Wang, Kai‐Xue; Chen, Jie‐Sheng
<x xml:space="preserve">Abstract</x> Uniform porous silicon hollow nanospheres are prepared without any sacrificial templates through a magnesiothermic reduction of mesoporous silica hollow nanospheres and surface modified by the following in situ chemical polymerization of polypyrrole. The porous hollow structure and polypyrrole coating contribute significantly to the excellent structure stability and high electrochemical performance of the nanocomposite. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>